Distorted octahedral sites drive early formation and stabilisation of nickel oxyhydroxides in trimetallic nickel–iron–molybdenum oxides - Rafei, Mouna; Piñeiro-García, Alexis; Wu, Xiuyu; Puentes-Prado, Elena; Ustunel, Tugce; Appelfeller, Stephan; Wågberg, Thomas; Gracia-Espino, Eduardo (Communications Materials, 2025)
Trimetallic nickel–iron–molybdenum oxides are excellent electrocatalysts for alkaline water electrolysis despite experiencing severe molybdenum dissolution. While the impact of molybdenum on fresh samples is well-understood, its substantial loss during operation without compromising performance presents a unique puzzle. Here, we show that the initial presence of molybdenum induces the formation of nickel vacancies and distorts octahedral nickel sites. This structural distortion induces charge transfer between lattice oxygen and nickel, inducing an early formation and stabilization of active nickel oxyhydroxides. Even after complete molybdenum leaching and transitioning into a bimetallic nickel-iron oxide, the catalyst retains its exceptional performance due to the persistence of distorted octahedral nickel sites. Understanding this process enables the exploration of alternative metals that could induce similar structural distortions, as well as inspire similar strategies in other electrocatalysts. (Figure presented.)